Viruses and prions of Saccharomyces cerevisiae - Wickner, Reed B. (2013)
Saccharomyces cerevisiae has been a key experimental organism for the study of infectious diseases, including dsRNA viruses, ssRNA viruses and prions. Studies of the mechanisms of virus and prion replication, virus structure and structure of the amyloid filaments that are the basis of yeast prions have been at the forefront of such studies in these classes of infectious entities. Yeast has been particularly useful in defining the interactions of the infectious elements with cellular components: chromosomally encoded proteins necessary for or blocking the propagation of the viruses and prions, and proteins involved in expression of viral components. Here we emphasize the L-A dsRNA virus and its killer-toxin-encoding satellites, the 20S and 23S ssRNA naked viruses, and the several infectious proteins (prions) of yeast.